Developing Correlates of Protection for Vaccines Is Needed More than Ever—Influenza, COVID-19 and RSV Infection - Zoltan Vajo; Csaba Laszlofy (Viruses)
One of the greatest success stories of modern medicine is the prevention of infectious diseases by vaccination, most notably against smallpox and poliomyelitis. However, recent events, such as the 2009–2010 swine flu and the 2020 COVID-19 pandemics, as well as the continued emergence of highly pathogenic avian influenza viruses highlighted the fact that we still need to develop new vaccines, and perhaps we should be proactive, rather than reacting to epidemics and pandemics. However, the development of tools for evaluating novel vaccines has not been able to keep up with the rate of vaccine production. Humoral and cellular immune responses to vaccination have both been suggested to be important in preventing infections or ameliorating their consequences, although there is uncertainty regarding their exact roles and importance. This, together with the rapid development of new vaccines, means that the need for developing immunogenicity parameters, and even more importantly, reliable correlates of protection, is more important than ever.